Collectivity, connectivity and control: reframing mass society in the digital era. Issue 1 (2nd January 2021) - Lee, Raymond L. M.
ABSTRACT: Mass society theory was originally a discourse on crowds, popular culture and revolutionary change. It portrayed the ideological control of the many by the few in situations of close contact without the complexities of mediated connectivity. The notion of social change was premised on analogue forms of collective behaviour within society rather than digital flows in networks. Reviving this theory in the digital era requires a reconsideration of connectivity and control transacted in mediated publics that support virtual gatherings centred on mass- self communication. Smartphones may be considered the iconic connectors that channel such communication. These electronic devices provide a vital understanding not only of the way information and communication technology is reshaping mass society but also the repositioning of the individual in networked relationships. It implies that mass in digitized environments is not simply a concept of nameless uniformity but one stressing the parasitic nature of networked connectivity. At the same time, it also suggests a connectivity made fragile by forms of remote control that are predatory on mass-self communication.